Effect of substrate temperature on the characteristic of p-PbI2 /n-Si heterojunction grown by pulsed laser deposition technique. (15th August 2019) - Ismail, Raid A.; Mousa, Ali M.; Shaker, Suaad S.
Abstract: Here we present the effect of the substrate temperature Ts on the characteristics of lead iodide nanostructured PbI2 film and p-PbI2 /n-Si heterojunction photodetector deposited by a pulsed laser deposition technique. XRD results show that PbI2 thin films deposited 27, 45 and 65 °C are polycrystalline in nature and have (001)-oriented PbI2 hexagonal structure (2H-polytype), while the film deposited at 100 °C was amorphous. The morphological study revealed that the film deposited at 45 °C was well-crystallized and has a uniform structure. Energy dispersive x-ray findings confirm the presence of Pb and I elements and the best stochiometry was observed for a film deposited at 45 °C. Raman spectra of PbI2 film show that all peaks belonged to PbI2 and the Raman intensity was found to be depended on the substrate temperature. As substrate temperature increases from 45 to 100 °C, the optical energy gap of the film decreases from 2.7 to 2.2eV. The electrical properties show that the deposited PbI2 films are p-type and the Hall mobility of the film decreases from 31 to 11cm 2 V − s −1 . The photoresponse results of the p-PbI2 /n-Si photodetector showed that the maximum responsivity was ∼ 410 mA/W at 610 nm for the photodetector prepared at 45 °C and a red shift in peak response of the photodetector was noticed when the substrate temperature increased to 100 °C.